1999
DOI: 10.1007/s004010051054
|View full text |Cite
|
Sign up to set email alerts
|

The N -methyl- d -aspartate receptor channel blocker amantadine does not cause histopathological alterations in human brain tissue

Abstract: Low doses of N-methyl-D-aspartate (NMDA)-type glutamate receptor antagonists induce morphological alterations in neurons of the cingulate gyrus and retrosplenial cortex of the rat. Neuronal cell death may result at higher doses. These effects are a major concern with regard to the introduction of new NMDA receptor antagonists into clinical trials. Amantadine is an uncompetitive NMDA receptor antagonist, which has been in clinical use for many years. In the present study we have looked for possible morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…The preclinical in-vitro and in-vivo studies available to date thus do not produce any clear evidence of neurotoxic effects of memantine (Kornhuber et al, 1994). Neither has the experience gained in clinical application with memantine provided any evidence of neurotoxic effects, as was also found for the NMDA channel blocker amantadine in histological investigations of the brain (Kornhuber et al, 1999). On the contrary, neuroprotective effects of memantine have been demonstrated in different in vivo and in vitro preclinical models (Seif el Nasr et al, 1990;Ferger and Krieglstein, 1996).…”
Section: Neurotoxic and Neuroprotective Effects Of Nmda Antagonistsmentioning
confidence: 98%
“…The preclinical in-vitro and in-vivo studies available to date thus do not produce any clear evidence of neurotoxic effects of memantine (Kornhuber et al, 1994). Neither has the experience gained in clinical application with memantine provided any evidence of neurotoxic effects, as was also found for the NMDA channel blocker amantadine in histological investigations of the brain (Kornhuber et al, 1999). On the contrary, neuroprotective effects of memantine have been demonstrated in different in vivo and in vitro preclinical models (Seif el Nasr et al, 1990;Ferger and Krieglstein, 1996).…”
Section: Neurotoxic and Neuroprotective Effects Of Nmda Antagonistsmentioning
confidence: 98%
“…Our study has also other limitations. It has been shown that both the gender of patients and the age of patients may influence amantadine efficacy in postoperative setting [21,23]. Although a posteriori power analysis of NRS comparisons revealed the power of 85.6% (at 1% alpha error level), taking into account the high variability of NRS, this study could not be powered enough to ultimately determine amantadine efficacy and should be considered as preliminary.…”
Section: Discussionmentioning
confidence: 86%
“…Amantadine is a well-known drug, commonly used in the treatment of Parkinson's disease; it shows also antiviral activity, which is exploited in the treatment of influenza type A. According to literature, amantadine in lower concentrations acts predominantly as an NMDA receptor antagonist, while in higher concentrations it can interact with other types of receptors, as well as may influence the release of dopamine from presynaptic bulb [13][14][15]21]. In our study, plasma levels of amantadine were relatively low, within range of action on NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the apparent neurotoxic effect of the NMDA receptor-antagonists MK-801, phencyclidine, ketamine and CPP, consisting in a vacuolization of the neuronal cytoplasm in cortical and subcortical regions, in the developing and adult rat brain, as well as in the primate brain (Fix et al, 1993;Ikonomidou et al, 1999;Sharp et al, 1994), raises concerns about the safety of these compounds in long-term clinical use. In contrast to these findings, a recent study by Kornhuber and colleagues could not observe histopathological alterations in the hippocampus, retrosplenial cortex or cingulate gyrus of PD patients treated with the open NMDA receptor channel blocker amantadine (Kornhuber et al, 1999). Currently, there are several glutamate antagonists under development providing very promising symptomatic and neuroprotective profiles, with respect to the protection against glutamate-mediated neurotoxicity.…”
Section: Novel Approaches In Antiglutamatergic Drug Developmentmentioning
confidence: 87%